2022
DOI: 10.1152/ajprenal.00296.2021
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential cation channel 6 contributes to kidney injury induced by diabetes and hypertension

Abstract: Diabetes (DM) and hypertension (HTN) are major risk factors for chronic kidney injury, together accounting for >70% of end-stage renal disease. In this study, we assessed whether DM and HTN interact synergistically to promote kidney dysfunction and if Transient Receptor Potential Cation Channel 6 (TRPC6) contributes to this synergism. In wild type (WT; B6/129s background) and TRPC6 knockout (KO) mice, DM was induced by streptozotocin injection to increase fasting glucose levels to 250-350 mg/dL. HTN was ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Under DKD conditions, signaling pathways such as PPAR, TGF-β, MAPK, and NLRP3 are activated in the renal tubules, and they transition from adaptive to pathological changes. We observed that klf10 and klf11 , which encode factors involved in the TGF-β signaling pathway [ 21 ] and inhibit cell growth, regulating extracellular matrix, and inducing cell apoptosis [ 22 , 23 ] are significantly upregulated in the proximal tubules. Consistently, the cell numbers in the PTS3 and PTS2 clusters were significantly lower in db/db mice than in db/m mice, this could be attributed to increased Klf10 and Klf11 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Under DKD conditions, signaling pathways such as PPAR, TGF-β, MAPK, and NLRP3 are activated in the renal tubules, and they transition from adaptive to pathological changes. We observed that klf10 and klf11 , which encode factors involved in the TGF-β signaling pathway [ 21 ] and inhibit cell growth, regulating extracellular matrix, and inducing cell apoptosis [ 22 , 23 ] are significantly upregulated in the proximal tubules. Consistently, the cell numbers in the PTS3 and PTS2 clusters were significantly lower in db/db mice than in db/m mice, this could be attributed to increased Klf10 and Klf11 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Along with other newly identified HDP-associated loci ( TNS2 55 and PLCE1 29 ), TRPC6 has also been linked to glomerular function. It has been implicated in focal segmental glomerulosclerosis and diabetic nephropathy 56 and mediates the proteinuria and renal dysfunction induced by exposure to hypertension and diabetes 57 . In addition, the progesterone receptor mediates the physiologic response to progesterone, including pregnancy-associated vasodilation 58 .…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that TRPC6 may function in conjugation with Protease-Activated Receptors (PARs) and GPCRs, contributing towards the development of glomerular injury and kidney disease in the patients presenting with diabetes. Notably, Wang et al found that the simultaneous induction of hypertension and streptozotocin-induced moderate diabetes in the same animal leads to markedly increased albuminuria and kidney injury compared to the conditions when hypertension and diabetes were induced separately, with genetic ablation of TRPC6 significantly reducing albuminuria and kidney injury [ 25 ]. Consistently, Spires et al also found that TRPC6 plays an important role in the development of DKD [ 26 ].…”
Section: Kidney Diseasementioning
confidence: 99%